(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Tasripin DS, Yuniarti E, Mutaqin BK. 2022. Isolation of indigenous microorganisms from the liquid produced by the bioprocess of corn straw as direct fed microbials. Biodiversitas 23: 3452-3456. Digestion of ruminants is highly dependent on microbial activity of rumen. Rumen microbes are responsible for degrading food nutrients into simpler components that can be easily utilized by the body. In order to improve the rumen ecosystem, the Direct Fed Microbials (DFM) was added. The addition of DFM to feed can be in the form of a mixture of several beneficial microbes (such as from the group of bacteria, yeast, and fungi) for the body of livestock. This group of microorganisms can be obtained from the results of the bioprocess of bioprocessed materials such as corn straw. In order to obtain the right microorganisms to be used as DFM, it is necessary to isolate the results of the bioprocess. The analysis was carried out by purification of indigenous microorganisms from the bioprocess of corn straw. Microbial purification can be done by isolation of microbes on agar media such as Nutrient Agar, MRS, and PDA by incubation to obtain a single cell. The results showed that isolation of the liquid from the bioprocess of corn straw was obtained in the form of Coccus and Bacilli which included gram-positive bacteria which were found to be dominant after incubation and microbial staining.